Are E-cigarette and tea cigarette gifting behaviors associated with tobacco use and failed quit attempts in China? - Zhou, Huan; Hoe, Connie; Zhang, Weifang; Yang, Xiaozhao; Li, Mingyan; Wu, Dan (International journal of environmental research and public health, 2022)
This study aims to investigate e-cigarette and tea cigarette gifting in China and their influencing factors, as well as to explore whether they were associated with tobacco use and cessation. Using a multistage sampling design, 1512 household heads from Guangdong and Shaanxi provinces were recruited for the study and filled out an online questionnaire about smoking status, social participation, e-cigarette, and tea cigarette gifting. Results showed that more than 30% and nearly 3% of participants had been gifted tea cigarettes and e-cigarettes, respectively. Marital status, province of residence, smoking status, and social participation were associated with gifting behaviors. Logistic regressions showed that receiving e-cigarettes (OR = 3.43, p < 0.05) and tea cigarettes (OR = 1.70, p < 0.01) were related to tobacco use. Smokers who have received e-cigarettes (OR = 9.85, p < 0.01) and tea cigarettes (OR = 1.92, p < 0.05) were also less likely to quit smoking.
Gesehen am 26.01.2023